Paradigma Sejahtera sebagai Acuan Pemeribumian Agenda Matlamat Pembangunan Lestari (SDG) - Ratna Roshida Ab Razak; Nur Ayuni Mohd Isa; Muhammad Hafeez Zakaria (USIM Press, 2024)
VOL. 8 NO. 1 Page (87-93)